DISEASES IN COASTAL COMMUNITIES IN INDONESIA: A REVIEW - Tosepu, Ramadhan; Effendy, Devi Savitri; Bahar, Hartati; Ali Imran, La Ode; Lestari, Hariati; Asfian, Pitrah (YCAB Publisher & IAKMI SULTRA, 2016)
Health services should be performed in all parts of Indonesia. Nationally, the people of Indonesia are scattered in several places, which are rural, urban, mountain, coastal, and others. Indonesia is the world's fourth most populous country, which might be a problem for national development because so many people are not accompanied by equitable growth. One of the problems is health care problem in coastal areas. This paper overview the diseases in coastal communities in Indonesia